Perancangan Aplikasi Augmented Reality Untuk Meningkatkan Berbahasa Batak Toba Pada Siswa Sekolah Dasar Dengan Metode Pembelajaran Gamefication - Heryanto Marpaung; Ari Usman; Arif Budiman (SNASTIKOM, 2023)
Many Indonesian cultures have changed in the current generation because they are considered ancient and ignore cultural customs. Unfortunately, the culture that has changed is one of the Batak cultures in the North Sumatra region. Even though the Batak culture originates from North Sumatra, there are still many children of the current generation who do not understand how to use the Batak language, let alone use the Batak language properly and correctly around us. This research created an application based on Augmented Reality (AR) which provides understanding and learning of Toba Batak culture and language as well as learning about Batak culture and Batak cultural customs. Augmented Reality is a technology that combines real-time computer-generated digital content with the real world. This research uses the gamification learning method used in this application to make learning the Toba Batak language culture more enjoyable in learning about Toba Batak culture and language properly and correctly and understand how to use the Toba Batak language well by providing a quiz game that involves the use of the language. Toba Batak can be understood well by children, children participate more actively in learning and experience an increase in Toba Batak language skills. In the end, a Toba Batak language culture learning application was created which aims to learn and know the Toba Batak language well and correctly which will be used by today's generation and improve the ability to speak the Toba Batak language well and correctly